Influence of Inorganic Fertilizers and Organic Amendments on Plant Nutrients and Soil Enzyme Activities under Incubation - Srinivasan, R.; Rao, K. Jeevan; Reza, S. K.; Padua, Shelton; Dinesh, D.; Dharumarajan, S. (International Journal of Bio-resource and Stress Management, 2023)
An incubation experiment was carried out in the department of Soil Science and Agricultural Chemistry, ANGRAU, Hyderabad, India during 2013−14 with 12 treatments including control to study the mineralization pattern and timely release of nutrients (N, P, K and soil enzymes) to plant from different sources and periods. Mineralization of nitrogen (NH4+-N and NO3--N), phosphorus (P2O5) potassium (K2O) and soil enzymes (urease, acid and alkaline phosphatase and dehydrogenase) activities from different treatments were evaluated. During initial period 7 to 21 days after incubation (DAI), the recommended dose of fertilizer (RDF) had maximum release of NH4+-N and NO3--N and later on decreased in the succeeding days but manures combination treatment has taken lead to release the N from 1 DAI to 70 DAI than control. Similar trends were followed in available P2O5 and K2O. The maximum quantity of urease and DHA were reached 203 to 227 µg NH4+-N g-1 soil h-1 and 10.6 to12.4 µg TPF g-1 soil h-1 from combination of poultry manure and neem cake at 70 DAI, respectively. Maximum released of acid and alkaline phosphatase were observed in 21 DAI and 35 DAI in RDF respectively. Among the manures treatment, PM+NC had superior in releasing of alkaline phosphatase over other, followed by poultry manure and FYM+PM. Correlation study between nutrients (N, P and K) and enzymes activity showed that a significant (p<0.05) positive relationship with each others.